Aspirin-Induced Ordering and Faster Dynamics of a Cationic Bilayer for Drug Encapsulation - Sahu, Samapika (Langmuir : the ACS journal of surfaces and colloids, 2023)
The lipid dynamics and phase play decisive roles in drug encapsulation and delivery to the intracellular target. Thus, understanding the dynamic and structural alterations of membranes induced by drugs is essential for targeted delivery. To this end, united-atom molecular dynamics simulations of a model bilayer, dioctadecyldimethylammonium bromide (DODAB), are performed in the absence and presence of the usual nonsteroidal anti-inflammatory drug (NSAID), aspirin, at 298, 310, and 345 K. At 298 and 310 K, the bilayers are in the interdigitated two-dimensional square phases, which become rugged in the presence of aspirin, as evident from height fluctuations. At 345 K, the bilayer is in the fluid phase in both the absence and presence of aspirin. Aspirin is preferentially located near the oppositely charged headgroup and creates void space, which leads to an increase in the interdigitation and order parameters. Although the center of mass of lipids experiences structural arrest, they reach the diffusive regime faster and have higher lateral diffusion constants in the presence of aspirin. Results are found to be consistent with recent quasi-elastic neutron scattering studies that reveal that aspirin acts as a plasticizer and enhances lateral diffusion of lipids in both ordered and fluid phases. Different relaxation time scales of the bonds along the alkyl tails of DODAB due to the multitude of lipid motions become faster upon the addition of aspirin. Our results show that aspirin insertion is most favorable at physiological temperature. Thus, the ordered, more stable, and faster DODAB bilayer can be a potential drug carrier for the protected encapsulation of aspirin, followed by targeted and controlled drug release with antibacterial activity in the future